Rooting for the underdog spectatorship and subalternity in Philippine basketball - Antolihao, Lou (Philippine studies : historical and ethnographic viewpoints, 2010)
"Basketball, "the tall man's game," is ironically the Philippines's most popular sports. The symbolic depiction of "small players" and their epic matches with bigger opponents mirrors the Filipinos' struggle against larger global forces, particularly amid colonization and underdevelopment. By looking into the celebrated Ginebra team and its throng of fans in the 1990s, this article demonstrates that basketball's popularity is hinged partly on its appeal as a subaltern spectacle. Basketball spectatorship has turned into a consuming diversion that celebrates the thrills of subversion and the possibilities of emancipation for millions of Filipinos who are burdened by everyday struggles against poverty and marginalization.